Nurses’ experience regarding patient safety in mobile pre-hospital care - Eduardo Dias Filipe; Roberto Chrispim Modesto; Hercules de Oliveira Carmo; Haviley Oliveira Martins; Maristela Santini Martins (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand nurses’ experience regarding patient safety in mobile pre-hospital care. Method: a qualitative, exploratory and descriptive study, conducted with nurses active in mobile pre-hospital care services. Semi-structured interviews were conducted, audio-graved and submitted to Bardin’s content analysis. Results: from four thematic categories established, nurses reported the care and management skills necessary to work in this service. They demonstrated a commitment to ensuring safe care for patients, staff and spectators. They highlighted the actions taken to prevent and mitigate incidents. However, they based their experiences on practice protocols and individual actions, expressing the need to improve knowledge about patient safety. Final Considerations: mobile pre-hospital care nurses’ experience in relation to patient safety was limited, suggesting the need for training on the subject, alignment of work processes and implementation of strategies, aiming to guarantee safe care.